Recent Advances in Characterization Techniques for the Interface in Carbon Nanotube-Reinforced Polymer Nanocomposites - Junjie Chen; Xuhui Gao; Deguang Xu (Advances in Materials Science and Engineering)
The current state of characterization techniques for the interface in carbon nanotube-reinforced polymer nanocomposites is reviewed. Different types of interfaces that exist within the nanocomposites are summarized, and current efforts focused on understanding the interfacial properties and interactions are reviewed. The emerging trends in characterization techniques and methodologies for the interface are presented, and their strengths and limitations are summarized. The intrinsic mechanism of the interactions at the interface between the carbon nanotubes and the polymer matrix is discussed. Special attention is given to research efforts focused on chemical functionalization of carbon nanotubes. The benefits and disadvantages associated with covalent and noncovalent functionalization methods are evaluated, respectively. Various techniques used to characterize the properties of the interface are extensively reviewed. How the mechanical and thermal properties of the nanocomposites depend on the physical and chemical nature of the interface is also discussed. Better understanding and design of the interface at the atomic level could become the forefront of research in the polymer community. Potential problems going to be solved are finally highlighted.